2020
DOI: 10.1016/j.hpb.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant mortality and morbidity following preoperative radiotherapy for hepatocellular carcinoma

Abstract: Background: Radiotherapy (RT) can be used for tumor downstaging and as a bridge to transplantation in hepatocellular carcinoma (HCC), but its effect on surgical complications is unknown. Therefore, we investigated post-transplant mortality and acute readmission rates in HCC with and without preoperative RT using the National Cancer Database (NCDB).Methods: After exclusion, 11,091 transplant patients were analyzed, 165 of whom received RT prior to transplant. Multivariable binomial logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…There were cases of diaphragmatic hernia, gastric perforation, and intra-abdominal hematoma, which were all found to be located distant from the radiation treatment field such that these areas received negligible radiation dose. This is consistent with the findings of the National Cancer Database analysis by Hasan et al, 28 which identified 165 patients treated with RT before LT without significant increase in perioperative mortality or hospital length of stay.…”
Section: Discussionsupporting
confidence: 91%
“…There were cases of diaphragmatic hernia, gastric perforation, and intra-abdominal hematoma, which were all found to be located distant from the radiation treatment field such that these areas received negligible radiation dose. This is consistent with the findings of the National Cancer Database analysis by Hasan et al, 28 which identified 165 patients treated with RT before LT without significant increase in perioperative mortality or hospital length of stay.…”
Section: Discussionsupporting
confidence: 91%
“…HCC is prone to metastasis and targeted therapy with liposomes has been shown to be effective ( 26 , 27 ). In recent years, targeted therapy has demonstrated the most effective results for HCC, and several targeted therapy drugs remain in clinical trials ( 28 ). In the present study, using TCGA database analysis and IHC staining assays, high KIF2C expression levels were identified in human HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…39 An analysis of 11 091 liver transplant patients within the NCDB identified 165 patients with HCC who received preoperative RT. 40 Although RT was more often delivered to larger tumors at more advanced stages, its use before OLT did not increase postoperative mortality or length of stay. Preliminary data from the first 29 patients treated in the Lahey Clinic randomized phase 2 trial (NCT02182687) of SABR versus TACE as bridging therapy pre-OLT has been reported in abstract form and showed that SABR may be associated with fewer days of inpatient admission and fewer retreatments.…”
Section: The Evolution Of Stereotactic Radiotherapy In the Management Of Hepatocellular Carcinomamentioning
confidence: 96%
“…An analysis of 11 091 liver transplant patients within the NCDB identified 165 patients with HCC who received preoperative RT 40 . Although RT was more often delivered to larger tumors at more advanced stages, its use before OLT did not increase postoperative mortality or length of stay.…”
Section: Indications For Stereotactic Ablative Body Radiotherapy In Hepatocellular Carcinomamentioning
confidence: 99%